6+17d=13d+18

Simple and best practice solution for 6+17d=13d+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+17d=13d+18 equation:


Simplifying
6 + 17d = 13d + 18

Reorder the terms:
6 + 17d = 18 + 13d

Solving
6 + 17d = 18 + 13d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-13d' to each side of the equation.
6 + 17d + -13d = 18 + 13d + -13d

Combine like terms: 17d + -13d = 4d
6 + 4d = 18 + 13d + -13d

Combine like terms: 13d + -13d = 0
6 + 4d = 18 + 0
6 + 4d = 18

Add '-6' to each side of the equation.
6 + -6 + 4d = 18 + -6

Combine like terms: 6 + -6 = 0
0 + 4d = 18 + -6
4d = 18 + -6

Combine like terms: 18 + -6 = 12
4d = 12

Divide each side by '4'.
d = 3

Simplifying
d = 3

See similar equations:

| 8(2.5+-4.5y)+3y=-13 | | (6-j)(6+J)= | | -132x-7x=8x+18 | | x+(x+13823)=119453 | | -3x+5y=12 | | 320+8x=7208-220x | | 3(6+5y)=2(-5+5Y) | | 105-5x=9x+2 | | (3/16+5/9)*24/30 | | 3/4/y=-7/48 | | 100x+2000=200x | | 2(2.5+-4.5y)+9y=5 | | 5/2(1-2x)+15/2=-4x | | 3+2(2x+5)=0 | | 1.6h-72=-3d+2 | | 3x^3-147=0 | | 9s^2+11s+4=0 | | -3(8)-4(0)= | | 4(3y-3)=6y-24 | | -3(n-2)=3n-5+9 | | 2x-5(0)=16 | | 2ln(-x)+8=16 | | 2(8+2.5y)=16 | | -42=-36t | | 0-3(0)=6 | | 6t+2=2(3t+1) | | y=7-x/2 | | 3z^2+5z+1=3 | | 2x+x+4x=1715 | | 4x-3-6x+2=0 | | 0.25t+0.833=1.5t+0.67 | | (7-2j)-(7+2j)= |

Equations solver categories